Improving Science Learning Outcomes About the Solar System Using the STAD Model Class VI SDN 1 Rawoh - Ekawati, Fransiska Tatiana Fitri (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This study purpose to improve learning outcomes in Science Theme 9 Sub-theme 2 about the solar system in grade VI students of SD Negeri 1 Rawoh, Karangrayung District, 2019/2020 academic year. This study uses a Classroom Action Research (CAR) model which is carried out in 2 cycles. The results showed that there was an increase in student learning outcomes using the STAD (Student Teach Achievement Division) cooperative method. In the pre-cycle stage of 24 students who achieved learning completeness 6 students (25%). Then in the first cycle of learning completeness reached 17 students (70.83%) and in the second cycle there was an increase to 23 students (95.83%). So the conclusion of this study shows that learning with the STAD type cooperative method improves science learning outcomes about the solar system in grade VI students of SD Negeri 1 Rawoh, Karangrayung District, semester II of the 2019/2020 school year.